Jak społeczność lokalna pod wpływem polityki regionalnej wykorzystała dziedzictwo – na przykładzie „Żywego Skansenu – Centrum Folkloru Polskiego w Nagawkach” - Andrzejczak, Barbara (Lodz University of Technology Press, 2016)
Revitalization should be a process with the effect of restoring an area to live and re-use and improving quality of life. Revitalization should be seen also as a way to protect heritage. The development of the theory of heritage has caused changing in thinking about the heritage that is understood today as a memory, choice and identity. The term heritage mean an everything that modern man has chosen from the past, that they created themselves for the purposes of the present day or to pass to future generations. Monuments are used in today’s world mainly for tourism. And that is acceptable way of earn money to provide maintenance and preservation of the monuments. To make the object more attractive for the viewers, owners often adapt monuments for the new functions, other than the original, which is interfering in authenticity of monuments. In my believe authenticity may be associated not only with the material and substance, but also the use and function, traditions and techniques, location and environment, and with the spirit and feelings to the object. An example of using the heritage by the local community with the help of local authorities that I’m presenting is the “Alive Open-Air Museum – Centre of Polish Folklore”, located ap. 30 km from the Łódź, 120 km from the Warsaw. The buildings that are in the museum were “unwanted” or inconvenient to the local governments. The main idea was to use this objects, and do not create another museum exhibition. And so it happened. This place offer you a wide range of services: accommodation, catering, banquets and special events, horse riding school, education and training centre and workshops. The project is still in progress, so they haven’t finished the construction yet. In open-air museum there are: wooden manor house from 19/20th century – translocated from Grodzisk (Dmosin), currently used as a Conference and Banquet Centre; in wooden cottage from 18/19th century from Brzeziny there is Cafeteria and Tearoom; in 20th century weaver’s house translocated from Zgierz there are two apartments on the first floor and restaurant on the ground floor; a historic cottage from Dobroń was saved from devastation, now it is a central kitchen which handles all receptions and events and also provides catering; in a former Mariavite Presbytery from the early 20th century there is management centre and in a reconstructed church originally combined with presbytery is a winter concert hall. There are also new buildings: stable with hotel rooms, amphitheatre which architecture has been entered into the natural lay of the land and pool’s complex with sauna. Recently was built lodge and wedding hall, which will support even more events. There are also plans to restore the 17th century church, in which, for example you will be able to get married or baptize a child. The project was realized with the help of EU funding under Regional Operational Programme of the Łódź Region for the years 2007-2013, Priority Axis III: Economy, Innovation, Entrepreneurship, Action III.5: tourism and recreation infrastructure. The total value of the project was 25 million PLN and the amount of grant from ROP was 10 million PLN. This place is really an amusement park, which was a really big commercial success. In my opinion this is not a good example of a new system of heritage protection because the commercial aspect of the complex of buildings has become more important than the cultural and educational function open-air museum.
How the local community influenced by regional policy used heritage on the example „Alive Open-Air Museum -Centre of Polish Folklore in Nagawki”
Keywords: revitalization urbanized areas; revitalization process; rewitalizacja obszarów zurbanizowanych; proces rewitalizacji